Congenital esophageal stenosis associated with esophageal atresia: A novel treatment - Maria Luisa Conighi; Cosimo Bleve; Lorenzo Costa; Salvatore Fabio Chiarenza (Elsevier, 2020)
Congenital esophageal stenosis (CES) is a very rare condition caused by ectopic tracheobronchial remnants (TBR), segmental fibromuscular hypertrophy (FMS) or membranous diaphragm (MD). In 25% of patients, CES is associated with esophageal atresia (EA). We present a challenging case report and we review the literature. Esophagogram conducted after a type III EA thoracoscopic correction, showed a sub-anastomotic CES 1 cm above cardia. EGDS confirmed it and CT-scan deposed for segmental fibromuscular hypertrophy. After conservative management failure (taper and balloon dilations), the patient underwent surgery through a laparoscopic approach. Intraoperative finding of a tracheobronchial remnant forced the surgeon to abandon the standard technique: because of the cardia proximity, esophageal resection and anastomosis were not possible without removing the cardia. New solution applied was successful: a postoperative contrast study and EGDS demonstrated CES resolution and, at one year follow up, the patient was symptom-free. The correct definition of CES anatomical features and position is critical to choose the best therapeutic approach. The technique we applied led to an anatomical and clinical resolution, but, as highlighted in literature, a longer follow up is needed to confirm the efficacy of treatment.